The impact of economic factors on the political system of modern Spain = Wpływ czynników gospodarczych na działanie systemu politycznego współczesnej Hiszpanii - Myśliwiec, Małgorzata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The main aim of this article is to try to predicate how seriously the economic factors have affected in the past and continue to affect at present the functioning of the Spanish political system. The autor of the text starts from the assumption that economic issues are very important for the operation of political system.
Keywords: Spain; economic crisis; political system; Hiszpania; kryzys gospodarczy; system polityczny